Spain : 2010 Article IV Consultation; Staff Statement; Staff Supplement; Staff Report; Statement by the Executive Director for Spain; and Public Information Notice on the Executive Board Discussion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
Spain's economy is facing severe challenges. Financial market tensions increased sharply in the wake of the Greek crisis. Policy should focus on rebalancing of the economy and securing market confidence. Ambitious fiscal consolidation is under way, but achievement of the targets needs to be made more credible and complemented by bold pension reform. A radical overhaul of the labor market is urgent. Progress in recent years on product and service market reform should continue. The banking sector remains sound but is under pressure.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet